2010
DOI: 10.1111/j.2042-3292.2009.00026.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the characteristics and treatment of methicillin‐resistant Staphylococcus aureus (MRSA) in the horse and a case series of MRSA infection in four horses

Abstract: Summary Methicillin‐resistant Staphylococcus aureus (MRSA) is an emerging cause of serious bacterial infection in the horse, with an increasing number of cases reported over the last decade. MRSA, along with other commensal staphylococcal species, can reside on the mucosa of several sites in the horse, particularly the nose. Nasal carriage of MRSA appears rare amongst horses in the community, although a higher prevalence has been found in hospitalised horses. MRSA infections can involve a variety of body sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 100 publications
(224 reference statements)
2
10
0
Order By: Relevance
“…Similar to another study, 28 MRSA was isolated from a variety of sites, with the majority (80%) from the skin/soft tissue and joints. Clinical infection with MRSA is a result of bacterial invasion and multiplication in a region that is not a usual commensal site.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar to another study, 28 MRSA was isolated from a variety of sites, with the majority (80%) from the skin/soft tissue and joints. Clinical infection with MRSA is a result of bacterial invasion and multiplication in a region that is not a usual commensal site.…”
Section: Discussionsupporting
confidence: 80%
“…Reports of prevalence rates in the general equine population vary. MRSA colonisation in clinically normal horses in the United Kingdom range from 0% to 6%, 28 and in North America, MRSA colonisation in horses ranges from 0% to 4.7%, 29,30 the latter including properties with a MRSA prevalence as high as 45%, reflecting a population where MRSA is endemic 30 . Currently, no studies have reported the prevalence of nasal colonisation in horses in the general population in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Such previous colonization was identified as risk factor for the development of subsequent clinical disease with MRS (Weese et al, 2006). Common infections caused by these opportunistic pathogens include soft tissue, musculoskeletal and infections (Corrente et al, 2009;Maddox et al, 2010;van Spijk et al, 2016 accepted). Production of ESBL in Enterobacte riaceae allows the isolate to open the b-lactam ring of cephalosporins, thereby inactivating them (Paterson and Bonomo, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to prior studies, MRSA in the present study were mainly responsible for incisional infections, phlebitis and synovial infections (Maddox et al . ). Methicillin‐resistant coagulase‐negative staphylococci have so far not been recognised as important pathogens in horses due to their inferior pathogenicity compared with S. aureus (Devriese et al .…”
Section: Discussionmentioning
confidence: 97%
“…Few studies on infections caused by MDR bacteria have been published in horses and most often they focused on methicillin-resistant Staphylococcus spp. (MRS) and extended-spectrum b-lactamases (ESBL)-producing Escherichia coli (Anderson et al 2009;van Duijkeren et al 2010;Maddox et al 2010;Dierikx et al 2012;Walther et al 2014). Both species have developed resistance towards b-lactam antibiotics, one of the most important antimicrobial classes in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%